Prevalence of work related injuries and its associated factors among workers of an undergarment manufacturing industry in Teluk Intan, Perak, Malaysia - Nkemakolam, Obi Adaeze (2017)
Industrial accidents are commonplace until today, there are thousands of workers getting injured every day. Workplace accidents and injuries do not happen by chance. Accidents and injuries happen as a result of interplay of many variables in the workplace, such as the worker, equipment, working procedures and many more. The key to prevent the accidents from happening would be to control the accident hazard and risk in the workplace. A cross-sectional study was carried out over a 3-month period from14th July 2016 to 1st September 2016 among workers in an undergarment manufacturing industry in Teluk intan, Perak to determine the prevalence and factors associated with work related injuries. Two hundred and fifteen workers 215/260 were selected which is 82.7% response rate by a two-stage simple random sampling. Questionnaires were validated using content and face validity. Self-administered, validated and pretested questionnaires in English and Bahasa Malaysia were used to determine the socio-demographic characteristics, occupational factors (work station, work environment), Organizational factors (safety training, administrative control) and behavioral factors (personal protective equipment availability and job task demand). The prevalence of work related injuries among the respondents was 73.5%. Male significantly reported with higher rate of work related injuries (82.1%) (p = 0.011). Malaysia reported with 64.1% of workplace injuries. Among non-Malaysia the prevalence of work related injuries was highest among Nepalese (91.7%) (p=0.004). Among Malaysian, Indian reported with highest incidence of work related injuries 87.5%, the association was significant association (p=0.028). The prevalence of work related injuries was the highest among divorced, widowed or separated with 84.6%. This was significantly associated with work related injuries (p=0.024). Logistic regression analysis found significant association between work related injuries and working with an electric motor which was one of the major predictors in this study ( AOR = 149.5, 95% CI =13.4-1668.1, p<0.001) and feeling tired and dizzy after work also. As well as, primary educational background (AOR = 196.1, 95% CI= 5.56 - 19.70, p= 0.004), noise (AOR = 7.80, 95% CI =2,13 - 28.6, p= 0.002), heat (AOR = 28.2, 95% CI = 2.21 - 358.8, p= 0.010 ) and adequate safety policies (AOR = 0.20, 95% CI = 0.06 - 0.65, p= 0.008). In conclusion, this study has identified that the prevalence of work related injuries is high among workers. To curb this high prevalence, guidelines and policies for preventive action should be put in place and training on the proper use of machine targeting workers with low educational background should be provided. The next step is to determine the causes of work related injuries among production workers and provide workers adequate work schedule to enable them have enough rest and avoid fatigue.